2018
DOI: 10.1016/j.lindif.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and longitudinal outcomes of spelling skills in individuals with histories of early speech and language disorders

Abstract: This study examined the spelling skills in middle childhood and adolescence in individuals with histories of early childhood speech sound disorders (SSD) with and without language impairment (LI). Youth without such histories were also included (No SSD/LI group). The heritability of spelling skills at each age level was estimated. Children with SSD were classified as SSD-only, SSD with LI but without childhood apraxia of speech (SSD + LI/ No CAS), and CAS and LI (CAS + LI). The SSD-only group did not differ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…The strongest replications were for a variety of measures collected in CFSRS with ALSPAC from older youth. Consistent with these findings, we previously demonstrated that spelling at later ages has a higher estimated heritability than spelling at school-age 11 . Measures administered in older youth may also be more sensitive to variations in clinical manifestation of SSD.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The strongest replications were for a variety of measures collected in CFSRS with ALSPAC from older youth. Consistent with these findings, we previously demonstrated that spelling at later ages has a higher estimated heritability than spelling at school-age 11 . Measures administered in older youth may also be more sensitive to variations in clinical manifestation of SSD.…”
Section: Discussionsupporting
confidence: 84%
“…of age 2 , with an estimated 3.8% of children persisting with speech delay at 6 years of age 3 . More than half of these children encounter later academic difficulties in language, reading, and spelling 7-11 . Because of the relative rarity of persistent speech problems and their correlation with other communication domains, endophenotypes are key to the study of genetic underpinnings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this population of children often experiences deficits in reading, spelling, and social-emotional well-being. [8][9][10][11][12][13][14][15] Thus, eligibility for services must take into consideration factors such as the connections between SSDs and reading 16 and the social implications of an SSD. Further, IDEA is explicit that eligibility is a team decision and that the team includes qualified professionals (e.g., classroom teacher, SLP) and the child's parent(s) ( § 614, b, 4, A).…”
Section: Special Education Services In Public Schoolsmentioning
confidence: 99%
“…Thus, speech, language, reading, and spelling measures are highly correlated and often have common genetic associations 7 , 8 . Moreover, speech and other communication phenotypes follow a developmental trajectory, where some speech and language disorders resolve with age, whereas others persist; genetic influences on the less easily resolved manifestations are generally stronger 12 , 13 . Because of the common genetic underpinnings and pathologic associations between speech and other communication phenotypes, it is conceivable that genetic replication interweaves with different communication measures.…”
Section: Introductionmentioning
confidence: 99%